Tragedi Manusia dan Kemanusiaan: Merajut Perdamaian dalam Perspektif Agama Buddha - Ponijan Liaw (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The human predicament, when distilled, boils down to three aspects: humans versus nature, humans versus other humans, and humans versus themselves. How can peace be attained if human attitudes remain entangled in these three types of conflicts? Upon deeper and wiser examination of the essence of teachings encapsulated within the framework of religion, none actually reject the honoring and exaltation of humanitarian values.